The Covid-19 containment effects of public health measures: A spatial difference-in-differences approach - Reinhold Kosfeld; Timo Mitze; Johannes Rode; Klaus Wälde (Journal of Regional Science, 2021)
The paper studies the containment effects of public health measures to curb the spread of Covid-19 during the first wave of the pandemic in spring 2020 in Germany. To identify the effects of six compound sets of public health measures, we employ a spatial difference-in-differences approach. We find that contact restrictions, mandatory wearing of face masks and closure of schools substantially contributed to flattening the infection curve. The significance of the impact of restaurant closure does not prove to be robust. No incremental effect is evidenced for closure of establishments and the shutdown of nonessential retail stores.
Keywords: 320; containment effects; Covid-19; public health measures; spatial difference-in-differences